Multicentric Reticulohistiocytosis: A Case Report of an Atypical Presentation in a 2‐Year‐Old. Issue 3 (26th February 2015) - Olson, Jaleh; Mann, Julianne A.; White, Kevin; Cartwright, Victoria W.; Bauer, Jeremy; Nolt, Dawn
Abstract Multicentric reticulohistiocytosis (MRH) is a rare systemic inflammatory granulomatous disease marked by severe and often rapidly progressive polyarticular arthritis and cutaneous papulonodules. Initial clinical diagnosis may be difficult. We describe a 2‐year‐old girl presenting with pink dermal papules on the forehead, thighs, elbows, knees, and palms of the hands. Based on clinical findings and skin biopsy results, she was initially diagnosed with granuloma annulare. At 5 years of age, she developed arthritis, fatigue, and more widespread skin papules leading to the diagnosis of MRH. To our knowledge, this is the youngest individual with MRH yet described. We outline the timeline and unique features of her case and review the literature pertaining to MRH in children. Although rare, MRH can be permanently debilitating, making prompt diagnosis critical. A standardized approach to investigation and management needs to be developed.